English Consonant Mispronunciations by Online Indonesian English Teachers in YouTube Channels - Rosari, Maria Dewi; Kusumawati, Arie (International Journal of Language Teaching and Education, 2026)
This study investigates English consonant mispronunciations among online Indonesian English teachers in YouTube-based instructional videos, mapping the specific phonemes most prone to distortion and identifying their underlying Second Language Acquisition (SLA) causes. Based on an analysis of 24 standard consonants, the findings reveal that only 11 phonemes were frequently mispronounced, culminating in 45 systematic deviations. A distinct hierarchy emerged: the voiced fricatives [z] and [v] exhibited the absolute highest error frequencies, while [t] and [θ] formed the prominent second tier. Viewed through SLA frameworks, these errors are driven by interlingual L1 carry-over regularities (final devoicing and cluster simplification), articulatory difficulties with non-native interdental targets, and intralingual overgeneralizations linked to irregular English orthography. These findings highlight a critical need for targeted contrastive phonology and orthographic decoupling in teacher training to arrest the digital transmission of fossilized errors.